2004
DOI: 10.1124/jpet.103.062216
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α-Induced Cytokine-Induced Neutrophil Chemoattractant-1 (CINC-1) Production by Rat Gastric Epithelial Cells: Role of Reactive Oxygen Species and Nuclear Factor-κB

Abstract: Rat cytokine-induced neutrophil chemoattractant-1 (CINC-1), a counterpart of the human growth-regulated oncogene product (GRO), has been suggested to participate in neutrophil recruitment in an experimental model of gastritis in rat. However, the mechanism(s) involved in regulation of CINC-1 production by the gastric mucosa remains unclear. The aim of this study was to investigate the mechanism(s) of CINC-1 production by rat gastric mucosa in vitro. All experiments were performed using rat normal gastric mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 36 publications
(43 reference statements)
2
41
0
Order By: Relevance
“…In addition to its acid-suppressing effects, lansoprazole have been shown to modulate the inflammatory status, reduce oxidative stress, and ameliorate mucosal injuries in the esophagus [23,24], intestine [25,26], and lung [27], in addition to the stomach [28,29]. It has been also demonstrated by in vitro studies that lansoprazole inhibits the increased expression of vascular adhesion molecules, the activation of neutrophils, and the production of pro-inflammatory cytokines from activated endothelial cells [30,31]. We recently demonstrated using in vivo models that lansoprazole inhibits acute inflammatory reactions as well as intestinal mucosal injuries induced by ischemia-reperfusion [25] or indomethacin administration in rats [26].…”
Section: Anti-inflammatory Effects By Lansoprazolementioning
confidence: 97%
See 1 more Smart Citation
“…In addition to its acid-suppressing effects, lansoprazole have been shown to modulate the inflammatory status, reduce oxidative stress, and ameliorate mucosal injuries in the esophagus [23,24], intestine [25,26], and lung [27], in addition to the stomach [28,29]. It has been also demonstrated by in vitro studies that lansoprazole inhibits the increased expression of vascular adhesion molecules, the activation of neutrophils, and the production of pro-inflammatory cytokines from activated endothelial cells [30,31]. We recently demonstrated using in vivo models that lansoprazole inhibits acute inflammatory reactions as well as intestinal mucosal injuries induced by ischemia-reperfusion [25] or indomethacin administration in rats [26].…”
Section: Anti-inflammatory Effects By Lansoprazolementioning
confidence: 97%
“…Our previous report demonstrated that rat gastric epithelial cells (RGM-1 cells) produced CINC-1 in response to various pro-inflammatory cytokines, such as TNF-α, IL-1β, and bacterial LPS [30]. To confirm the anti-inflammatory effect of lansoprazole-induced HO-1 on RGM-1 cells, we measured the production of CINC-1 on RGM-1 cells using ELISA.…”
Section: Anti-inflammatory Effect Throughout Ho-1 Induction By Lansopmentioning
confidence: 99%
“…Cytokineinduced neutrophil chemoattractant-1 (CINC1), which corresponds to human interleukin-8 (IL-8), is a key cytokine in the rat. Previous studies showed that CINC1 protein plays an important role in rat gastric inflammation induced by H. pylori infection (17).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their findings, they speculated that the oxygen radicals produced following I/R of the liver stimulate Kupffer cells to release CINC-1. We have shown direct evidence of the involvement of ROS in the signaling pathway of CINC-1 production in an in vitro model of gastric inflammation: in which we demonstrated that TNF-α-induced CINC-1 production in a rat gastric mucosal cell line (RGM-1) is an event mediated by oxidative stress and is dependent on NFκB activation [37].…”
Section: Oxidative Stress-mediated Cell Signal Transductionmentioning
confidence: 95%